Clinical Training for Medical Physicist: Implementation Experience in Bangladesh (Bangladesh Journal of Nuclear Medicine, 2017)
It is very important that the medical physicists working in hospitals need to be clinically trained.Bangladesh was the first RCA member to implement clinical training programme based on the guide-book for medical physicists specializing in nuclear medicine developed by International Atomic Energy Agency. A National Program was established and Bangladesh Medical Physics Association agreed to be the Professional Body for accreditation. The 2 years pilot to test the effectiveness of the guidebook was successfully finished. The Clinical Training for medical physicists specializing in nuclear medicine improved the capabilities of the Physicits’. A sustainable accreditation structure is in place. The objective of the program was to set up an infrastructure to operate an independent and sustainable accreditation programme that is recognized by all in Bangladesh and to test out the effectiveness of the guidebook in providing clinical training to medical physicists specializing in nuclear medicine.Bangladesh J. Nuclear Med. 18(1): 69-72, January 2015